2019
DOI: 10.1007/s12144-019-00363-1
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, sense of coherence and self-efficacy as predictors of stress coping style among university students

Abstract: The purpose of this study was to identify the personality predictors of individuals with a stress coping style. In the study, we have attempted to establish which traits play a crucial role in the prediction of tendencies applicable to a specific style of stress coping. In this study, all personality predictors were included in one model. The study was conducted with a group of 632 students. The results demonstrate a positive relationship between both self-efficacy and resilience with a task-oriented style of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 44 publications
(65 reference statements)
10
40
0
2
Order By: Relevance
“…Although avoidance coping is known as a maladaptive avoidance strategy, some forms of this strategy might actually be healthy [ 92 , 93 ]. Contrary to avoidance behaviours such as stopping, distracting, or withdrawing, avoidance coping related to seeking contact with others, reading books, or doing work can be adaptive [ 94 , 130 ]. These healthier forms of coping do not necessarily approach the problem directly, but they do affect the response to the problem [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although avoidance coping is known as a maladaptive avoidance strategy, some forms of this strategy might actually be healthy [ 92 , 93 ]. Contrary to avoidance behaviours such as stopping, distracting, or withdrawing, avoidance coping related to seeking contact with others, reading books, or doing work can be adaptive [ 94 , 130 ]. These healthier forms of coping do not necessarily approach the problem directly, but they do affect the response to the problem [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Avoidant style can also be analysed in terms of its two forms (engaging in substitute activities and seeking social contact). Only then was the positive relationship between resilience and social contact seeking confirmed, while the relationship between engaging in substitute activities was insignificant (Konaszewski et al, 2019). In the course of other studies, the relation between resilience and task-oriented strategies of coping was also confirmed, and negative with emotion-oriented strategies (Beasley et al, 2003;Chen, 2016;Craparo et al, 2018;Konaszewski et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Only then was the positive relationship between resilience and social contact seeking confirmed, while the relationship between engaging in substitute activities was insignificant (Konaszewski et al, 2019). In the course of other studies, the relation between resilience and task-oriented strategies of coping was also confirmed, and negative with emotion-oriented strategies (Beasley et al, 2003;Chen, 2016;Craparo et al, 2018;Konaszewski et al, 2019). Our research also confirms previous findings, in terms of which resilience is also negatively associated with the perceived of stress and risk of depression, while positively with satisfaction with life (Beasley et al, 2003;Ahern et al, 2006;Abolghasemi and Varaniyab, 2010;Salazar-Pousada et al, 2010;Tempski et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The study of Akanni and Otakpor (2016) revealed a negative association between resilience and the psychological distress of school going adolescents in Benin, Nigeria. Other studies have demonstrated a positive and significant correlation between resilience and reduced task-based stress (Harms et al, 2018;Konaszewski et al, 2019;Memarian et al, 2015). Conversely, some other studies have shown that resilience also correlated negatively with some factors such as avoidance/ denial, distraction, self-blaming, and chronic depression (M. M. Smith et al, 2016;Stratta et al, 2015).…”
Section: Resilience and Psychological Wellbeingmentioning
confidence: 89%